Synbiotic containing extensively hydrolyzed formula improves gastrointestinal and atopic symptom severity, growth, caregiver quality of life, and hospital‐related healthcare use in infants with cow's milk allergy. Issue 6 (19th May 2022) - Hubbard, Gary P.; Atwal, Kiranjit; Graham, Lynne; Narayanan, Sankara; Cooke, Lisa; Casewell, Catherine; Denton, Sally‐Ann; Gavin, Joan; Browne, Robert M.; Kinnear, Fiona J.; McHardy, Ailsa J.; Evans, Debbie; et al.
Abstract: Background: Healthy gut microbiota is important for prognosis in cow's milk allergy (CMA). The application of synbiotics (specific pre‐ and probiotics) in extensively hydrolyzed formulae (eHFs) is a relatively new concept. Aims: To evaluate a synbiotic‐containing, whey‐based eHF (SeHF) with galacto‐oligosaccharides, fructo‐oligosaccharides, and bifidobacterium breve M‐16V in infants with CMA. Materials and Methods: A 31‐day one‐arm pilot study in 29 infants with CMA (mean age 30.8 weeks [SD 11]) was undertaken, with outcomes including gastrointestinal tolerance, atopic dermatitis symptoms, dietary intake, growth, SeHF acceptability, caregiver quality of life, and hospital‐related healthcare use. Results: Significant improvements ( p < .05) in the severity of abdominal pain (in 57%), burping (in 46%), flatulence (in 79%), constipation (in 14%), rhinitis (41%), and itchy eyes (73%), as well as atopic dermatitis in those with severe baseline symptoms (PO‐SCORAD © reduction: 34.7–18.2 ( p = .003), n = 6) were observed over time. Growth and caregiver quality of life scores significantly increased (+26.7%, p < .05) over time. Hospital visits and medications significantly reduced (−1.61 and −2.23, respectively, p < .005) in the 6 months after SeHF initiation. Discussion: In this small, single‐arm, pilot study, the use of SeHF enhanced the management of infants with non‐IgE mediated CMA who were already established on eHF. Conclusion: Whilst this study adds to the evidence base for the use of SeHF in CMA, further robust research to explore the longer‐term benefits of synbiotics, specifically the blend used in this study, for the clinical management of infants with CMA is warranted. Abstract : The application of synbiotics (specific pre‐ and probiotics) in extensively hydrolyzed formula (SeHF) is a relatively new concept. This study investigated the use of SeHF in 29 infants with non‐IgE mediated Cow's Milk Allergy and showed improvements in gastrointestinal and atopic symptoms, caregiver quality of life, and reduced healthcare use. The use of SeHF enhanced the management of infants with non‐IgE mediated cow's milk allergy